IDENTIFIKASI SAMPEL CORING ASPAL DENGAN METODE PEMBORAN DI PIT WINTO PADA WILAYAH TAMBANG PT. WIKA BITUMEN IUP KABUNGKA - Lanto, Muh. Said (SAINFIS: Jurnal Sains Fisika, 2022)
This research was conductied in the mining area of ​​PT. Wika Bitumen Pit Winto Banabungi Village, Pasarwajo Buton, Southeast Sulawesi Province which aims to determine the asphalt exploration process in the PT. Wika Bitumen Pit Winto mining area, to determine the stages in drilling and to determine the physical characteristics of asphalt samples obtained from drilling results. The research method consisted of the initial survey, mapping outcrops, and drilling results. The results showed that at the KF-21-039 point, most asphalt was found at a depth of 1.00 m – 7.80 m with a dark black asphalt color accompanied by a pungent odor that was not sticky. Meanwhile, at a depth of 7.80 m – 23.60 m, siltstone was found with a bluish-gray color, odorless, and not sticky. At a depth of 23.60 m – 25.20 m, another type of asphalt was found with black color, black spout, massive, pungent smell, and not sticky. From a depth of 25.20 m – 39.80 m, no asphalt was found, but siltstone.